The Effect of Growth Opportunity, Profitability, CSR, Firm Size, And Leverage on Earning Response Coefficient - Eny Kusumawati; Adinda Putri Wahyuningtyas; Shinta Permata Sari (Universitas Muhammadiyah Surakarta, 2022)
The earnings response coefficient (ERC) measures the magnitude of a stock's abnormal return in response to the abnormal earnings components (unexpected earnings) reported by the company that issued the stock. This study, thus, aims to analyze the effect of growth opportunity, profitability, corporate social responsibility (CSR), company size, and leverage on the earnings response coefficient (ERC) in manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2021 period. The sampling technique used in this study was purposive sampling. The sample of this study consisted of 180 companies that met the criteria as the unit of analysis. The analytical method employed was multiple linear regression analysis. The study results provide empirical evidence that CSR, firm size and leverage affected the earnings response coefficient. Meanwhile, growth opportunity and profitability did not affect the earnings response coefficient.